The troglophilic population of Lithobius peregrinus Latzel, 1880 (Chilopoda, Lithobiomorpha) from Gaura cu Muscă Cave – first record of the species in Romania: morphological variations, asymmetry, teratology and behaviour - Ștefan Cătălin Baba; Andrei Giurginca; Rodica Plăiașu; Robert Opran; Andreea Mîrleneanu; Octavian Pacioglu (Subterranean Biology)
The current study presents the first confirmed record of Lithobius peregrinus Latzel, 1880, in Romania, based on specimens collected from Gaura cu Muscă Cave (Banat Mountains). Over a three–year period (2022–2024), 39 specimens were sampled, revealing significant morphological variations, asymmetries, and teratological features. Morphological assessments, including variations in ocelli count, coxosternal teeth, plectrotaxy, and gonopod structures, were conducted. Directional asymmetry was analyzed, showing significant right–side bias in antennal segment counts but no clear asymmetry in other measured traits. Behavioural observations highlighted the close water affinity of this centipede, with individuals frequently found near water bodies, possibly contributing to its dispersal ability. The study also discussed the broader cave affinities of L. peregrinus, comparing its current geographic distribution to related species and highlighting changes in the cave microclimate that may have impacted its subterranean adaptations. These findings contribute to the understanding of the ecological preferences and morphological diversity of the species, enhancing the knowledge of centipede biodiversity in Romania.